Revista digital sobre la gráfica popular como manifestación cultural y creación de identidad en Tumbaco (Centro) - Galárraga Gallardo, Rosana Michele (2015)
Tumbaco is a rural parish that has gained importance in recent years, its population has increased considerably, and the same thing has happened to a commercial level. Tumbaco center still retains the characteristics of a small parish and community spirit, that is why in this context the study of popular graphic and its coexistence with standardized modes of communication is addressed. The development of this work involved extensive documentary review allowing the understanding of the graphic as an element of outside the mass media, which provides naturalness, ownership and creativity, also a collection of the graphic found in the sector took place, and which had greater cultural and identity representation was selected. Once selected the pieces, they were testing with the application of the Panofsky matrix. The creation of the digital magazine is a form of collecting the popular graphics of Tumbaco, but beyond functioning as a repository, this virtual space is presented for the diffusion of the cultural value and identity of the graphic. The magazine presents a space dedicated to articles, notes and interviews related to the theme of the popular graphics and an image gallery.